2018
DOI: 10.1038/s41598-018-21989-4
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale patterning of single cells and cell clusters in hydrogels

Abstract: Biophysical properties of the extracellular matrix (ECM) are known to play a significant role in cell behavior. To gain a better understanding of the effects of the biophysical microenvironment on cell behavior, the practical challenge is longitudinally monitoring behavioral variations within a population to make statistically powerful assessments. Population-level measurements mask heterogeneity in cell responses, and large-scale individual cell measurements are often performed in a one-time, snapshot manner … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Engineering surface topography to provide a niche that mimics the native context of cells is being actively exploited for biomedical research, including tissue engineering using single and/or multiple cell types [59]. Previously, entrapment of single cells and/or cell clusters with 3D micropatterns was piloted to be used in cancer research [60] and drug screening [61] with very limited use in the cardiac field. Previous studies showed the relationship between biophysical cues and CMs in many settings.…”
Section: Discussionmentioning
confidence: 99%
“…Engineering surface topography to provide a niche that mimics the native context of cells is being actively exploited for biomedical research, including tissue engineering using single and/or multiple cell types [59]. Previously, entrapment of single cells and/or cell clusters with 3D micropatterns was piloted to be used in cancer research [60] and drug screening [61] with very limited use in the cardiac field. Previous studies showed the relationship between biophysical cues and CMs in many settings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] However, this technique allows the cell spheroids to be arranged exclusively in a 2D structure, and often with only a single type of spheroid. [ 7,10 ] Alternatively, a magnetic field‐based technique has been introduced to create patterns with cell aggregates. [ 11 ] Although this technique allows the patterned spheroids to be induced within a short time in a 3D environment, several researchers have reported that the integrity of the cell aggregates is reduced when the field disappears; moreover, the technique cannot produce patterns that incorporate multiple cell aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the epithelial-mesenchymal transition (EMT) is associated with weakened cell-cell junctions and increased cellmatrix adhesions, driving tissue disorganization and dissemination (2). Remarkably, multicellular clusters cultured ex vivo in compliant 3D hydrogels can exhibit tissue-like form and function (3)(4)(5)(6)(7), representing a promising preclinical testbed for higher-throughput drug discovery and development (8,9). However, existing assays for 3D mechanophenotyping have been limited to a few cells per experiment due to the need for high-resolution optics and labor-intensive image processing, as well as complex readouts of force generation (10).…”
Section: Epithelial Tissues Mechanically Deform the Surrounding Extramentioning
confidence: 99%